Silencing of Long Non-coding RNA NEAT1 Upregulates miR-195a to Attenuate Intervertebral Disk Degeneration via the BAX/BAK Pathway - Tang, Ning; Dong, Yulei; Liu, Jiaming; Zhao, Hong (Frontiers in Molecular Biosciences, 2020)
Background/Aims:Increasing evidences have demonstrated that long non-coding RNAs (lncRNAs) play a vital regulatory role in the intervertebral disc degeneration (IVDD). Nuclear enriched abundant transcript 1 (NEAT1), as a novel cancer-related lncRNA, is associated with many malignancies including ovarian cancer, esophageal squamous cell carcinoma and so on. Nevertheless, the role of NEAT1 in the progression of IVDD remains to be studied. Here, we explored the effect and mechanism of NEAT1on the progression of IVDD. Methods: The IVDD model was constructed in SD rats in vivo and the degeneration was induced by advancedglycationend (AGE) in human nucleus pulposus cells (HNPC) in vitro. Quantitative Real-time PCR was performed to detect the relative NEAT1 and miR-195a expression, and further confirmed the relationship between NEAT1 and miR-195a. Cell apoptosis was evaluated by TUNEL assay. The related mechanisms were explored by western blot assay. Results:The relative NEAT1 expression was significantly up-regulated in the IVDD rat model and the denatured HNPC. Silencing of NEAT1 expression in HNPC significantly promoted the Collagen II and TIMP-1 expression induced by AGE, meanwhile greatly suppressed the expression of MMP-3 and cleaved caspase-3. Besides, down-regulation of NEAT1 obviously reversed the AGE-induced apoptosis in HNPC. More interestingly, these effects of knockout NEAT1on HNPC were largely reversed by silencing of miR-195a or overexpression of BAX under the AGE treatment. Mechanically,direct combination of NEAT1 with miR-195a resulted in up-regulation of MMP-3, cleaved caspase-3, BAX and BAK, as well as down-regulation of Collagen II and TIMP-1, which are associated with EMT and apoptosis. We also demonstrated these similar results in in vivo experiments. Conclusion:NEAT1 exerted as an onco-gene during the IVDD progression through mediating the miR-195 expression and might be used as a potential target for the IVDD therapy.